2022
DOI: 10.3390/bs12020033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mind-Body Interventions on Adolescents’ Cooperativeness and Emotional Symptoms

Abstract: Background: Mind-body interventions may support the development of adolescents’ self-regulation and provide a protective effect against maladaptive outcomes, e.g., internalizing and externalizing problems. The present study aimed at evaluating the effects of mindfulness-oriented meditation training (MOM) and autogenic training (AT) on a group of healthy Italian adolescents’ character dimensions, emotional and behavioral difficulties. Methods: 72 adolescents were randomly assigned to MOM/AT conditions and teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
4
0
1
Order By: Relevance
“…The mental health screening showed a significant increase in emotional self-regulation, which supported the efficacy of both meditation programmes. Emotional self-regulation, in turn, showed a correlation with cooperativeness [153]. What is most remarkable about the study is that there were changes in personality traits.…”
Section: Tablementioning
confidence: 64%
“…The mental health screening showed a significant increase in emotional self-regulation, which supported the efficacy of both meditation programmes. Emotional self-regulation, in turn, showed a correlation with cooperativeness [153]. What is most remarkable about the study is that there were changes in personality traits.…”
Section: Tablementioning
confidence: 64%
“…Meta‐analyses support the effectiveness of mind–body approaches for improving mental and physical health in the general population (Feruglio et al, 2022; Perrier et al, 2020; Section on Integrative Medicine, 2016). For example, data from 209 mindfulness‐based therapy trials indicated moderate effectiveness compared to no intervention and other active treatments, including psychological treatments, for anxiety, depression, and stress, with efficacy comparable to that observed for cognitive behavioral therapy and antidepressants (Khoury et al, 2013).…”
Section: Mind–body Interventions: the “What” “How” And “Why”mentioning
confidence: 99%
“…Finally, emotional disorders are common among adolescents. A recent study [23] has demonstrated that both two 8-week mind-body interventions, namely mindfulnessoriented meditation training and AT, resulted in an increased level of adolescents' cooperativeness (i.e., the acceptance of others, compassion, forgiveness) and reduced emotional difficulties (e.g., feeling unhappy, downhearted). The increases in cooperativeness following the AT correlated well with reductions in negative emotional symptoms [23].…”
Section: Effects Of Autogenic Training On Mood Disordersmentioning
confidence: 99%